2019
DOI: 10.1111/srt.12817
|View full text |Cite
|
Sign up to set email alerts
|

Ros‐NET: A deep convolutional neural network for automatic identification of rosacea lesions

Abstract: BackgroundRosacea is one of the most common cutaneous disorder characterized primarily by facial flushing, erythema, papules, pustules, telangiectases, and nasal swelling. Diagnosis of rosacea is principally done by a physical examination and a consistent patient history. However, qualitative human assessment is often subjective and suffers from a relatively high intra‐ and inter‐observer variability in evaluating patient outcomes.Materials and MethodsTo overcome these problems, we propose a quantitative and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Previous efforts have been made to apply CNN to identify rosacea. However, previous work focused mainly on the development of networks or analysis of images instead of practically applying CNN for the identification of rosacea and differentiating it from other skin diseases or for the classification of subtypes of rosacea [32]. Besides, the number of images for model development was quite limited (less than 100) in the previous studies and the sensitivity or specificity were barely satisfactory [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts have been made to apply CNN to identify rosacea. However, previous work focused mainly on the development of networks or analysis of images instead of practically applying CNN for the identification of rosacea and differentiating it from other skin diseases or for the classification of subtypes of rosacea [32]. Besides, the number of images for model development was quite limited (less than 100) in the previous studies and the sensitivity or specificity were barely satisfactory [33].…”
Section: Discussionmentioning
confidence: 99%
“…We used mini-batches of size 16 for U-Net. Early stopping was employed to avoid over-fitting [29, 30].…”
Section: The Proposed Methodologymentioning
confidence: 99%
“…This is a notable limitation considering that the incidence of scalp psoriasis is 45-56% and nail psoriasis is 23-27% among psoriatic patients [57]. CNNs have been created for other diseases, such as atopic dermatitis [58], onychomycosis [56], and rosacea [59]. To classify onychomycosis, Han et al [56] used a R-CNN to generate a training datasets of 49,567 images of nails and found that a combination of their datasets performed better than dermatologists.…”
Section: Other Dermatological Diseasesmentioning
confidence: 99%